MORPHOLOGICAL AND MORPHOMETRIC VARIATIONS OF SPLEEN: A CADAVERIC STUDY IN NORTH INDIAN POPULATION - NEELAM BALA; KULBIR KAUR; JAGDEV SINGH KULLAR; IPSHITA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of study is to study morphological and morphometric analysis of spleen and its clinical importance. Spleen consists of a large encapsulated vascular organ and important lymphatic tissue in the human body. Its immunological functions are being well realized. The weight, size, and shape of the spleen vary in human being with age, sex, and under different conditions in the same individual. The morphological variations are important for physicians, surgeons, and radiologists to avoid misinterpretation of the splenic variants. Methods: A cross-sectional study of a total of 50 adult human cadaveric spleens was done in the Department of Anatomy Government Medical College, Amritsar, Punjab. The study observed the morphological features such as shape, anomalous fissures, and morphometric measurements such as length, breadth, thickness, and weight of all the spleen specimens. Results: The wedge-shaped spleen constituted 62%, tetrahedral (30%), triangular (4%), and irregular (4%), shaped spleens. Out of 50, 60% displayed notches on the superior border of spleen and 10% on inferior border of spleen. There was no notch in 30% of the specimens. Mean length of spleen was 9.2 cm, mean breadth was 6.2 cm, and thickness was 3.08 cm, respectively. The mean weight of the spleens was 140.008 g. Anomalous fissures were 2% found on the diaphragmatic surface. Conclusion: The findings of the present study will be of fundamental importance to the physicians, surgeons, and radiologists and give clues for various clinical diseases.